Prevention and treatment of cerebral vasospasm following aneurysmal subarachnoid hemorrhage - Kyle McGrath; Grace Hey; Ghaidaa Ebrahim; Noah Gilberstadt; David Mahan; Brandon Lucke-Wold (Academia Biology)
Cerebral vasospasm after aneurysmal subarachnoid hemorrhage (aSAH) remains a significant cause of morbidity and mortality. Post-hemorrhage cerebral vasospasm (PHCV) occurs through a complex pathophysiology, and numerous pharmacologic agents, including vasodilators, anti-inflammatories, and fibrinolytics, as well as endovascular techniques have been used to prevent and/or treat PHCV. Nimodipine continues to be the only agent with level 1 evidence, but other vasodilators have demonstrated promising results. Endovascular therapy likely has a role in treating severe/refractory PHCV, but randomized trials are needed to establish stronger evidence for this therapy. Numerous preclinical investigations highlight novel targets related to the immune response that could prove effective at improving outcomes in clinical trials. Further investigation of the glymphatic system and its role in PHCV pathogenesis could result in novel pharmacologic targets. Future trials of these therapies and combinations of existing therapies are needed, and functional outcomes should be included as an endpoint. Further exploration of the neuroinflammatory reaction following aSAH will continue to identify targetable molecules involved in PHCV pathogenesis.